Strategi Pengembangan Wisata Budaya Berbasis Tradisi Kamooru Wuna di Kabupaten Muna - Sitti Hermina; Wa Kuasa Baka; Usman Rianse; Muhammad Iqbal Kusuma Baka Rianse (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
Cultural tourism has become one of the most dynamic sectors in the global tourism industry. Muna Regency has a variety of traditions that can be used as cultural tourism, one of which is the kamooru wuna tradition. In addition to its woven fabric products (kamooru), weaving activities can also be an exciting cultural tourism attraction because the process and tools used are still traditional. For kamooru wuna to succeed as a leading tourism commodity and to preserve this craft, it is necessary to conduct a study aimed at identifying the prospects for developing kamooru wuna-based cultural tourism and formulating strategies for developing cultural tourism based on the kamooru wuna tradition. This research was conducted in Muna Regency. Data collection was conducted through observation, in-depth interviews, literature reviews, and focus group discussions. Informants were determined using snowball sampling. Data analysis used qualitative descriptive analysis and SWOT analysis methods. The results of the study show that the Kamooru Wuna tradition can be utilized as a cultural tourism offering that incorporates elements of authenticity, uniqueness, quality, characteristic products, and a source of pride for the region, as well as a diverse range of tourist attractions. Based on the results of the SWOT analysis and FGD, several strategies were formulated for the development of cultural tourism based on the kamooru wuna tradition in Muna Regency, namely: 1) Development of the appeal of kamooru Wuna and the Masalili Weaving Tourism Village, 2) Addition of tourism support facilities and environmental cleanliness, 3) Development of integrated cultural tourism (agro-tourism and rural tourism), 4) Developing human resources and strengthening institutions, and 5) Developing local cotton and yarn centres in Muna Regency.